Keragaman Genetik dan Penampilan Jagung Hibrida Silang Puncak pada Kondisi Cekaman Kekeringan - Azrai, Muhammad; Efendi, Roy; Suwarti, Suwarti; Praptana, R. Heru (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Wide diversity genetic materials is required to develop new superior drought tolerant maize. The objective of this experiments were to obtain genetic diversity information,heritability value and to find out yield character performance, yield component and Agronomic traits performance of top cross maize severe drought stress. One hundred and fifty maize  genotypes of top cross selection  and four hybrid maize as check varieties, were tested to obtained the Agronomic trait performance in Probolinggo of East Java and Gowa district of South Sulawesi in dry season of 2013. Factorial Randomized block Design with two replication was used in this experiment. Each hybrid grown one plant per hole in two rows of 5 m length plot,  placed in 70 cm between row space and 20 cm between row. The result of this research showed that top cross hybrid had different significantly response under drought stress, eventhough genotypes had low genetic diversity. Heritability probability of broad sense of silking, ear row number, and shelling percentage were high, wherease in the mid heritability showed traits of 50% anthesis, anthesis-silking interval, plant height, ear height, weight and ear performance, ear length, 1000 seeds weight and yield. The 20 best hybrids according to the highest grain yield, were 17 genotypes which had good combining ability with P21, 2  genotypes had good combining ability with Bima 11 and only one genotype had good combining ability with both of top cross parent (P21 and Bima 11). The yield rates of 20 top cross hybrids in Probolinggo spreaded at 4.8 t/ha – 6.7 t/ha significantly higher than tester variety, wherease yield rates in Gowa  ranged at 4.5 t/ha – 6.7 t/ha and only 4 tested hybrids within significantly superior than four tester variety. For the purpose of further selection, determining of the best C1 genotype should be done per location due to large environmental effect.